Annual Report 2013-14 Planning Commission Government of India - Planning Commission (Planning Commission, 2013)
The resolution in its paragraph 6 highlighted the need for an advisory body at the highest policy level, free from the burden of the day-to-day administration, but in constant touch with the Central government and State Governments which would help meet the fundamental rights guaranteed to the citizens and secure the directive principles of the State Policy
Planning Commission Government of India
Planning Commission Government of India